PENGARUH HARGA SAHAM PERUSAHAAN TERHADAP TRANSAKSI JUAL BELI SAHAM DI PASAR MODAL INDONESIA - Yunita Astikawati; Dessy Triana Relita (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2017)
This research aim at exploring the influence of company’s share price to the share transaction at Indonesian share market. The company's share price has been measured by using MBV, EVA, MVA, PER and dividend-discount model. Share market transactions have been measured using the volume and frequency of share trading. The data of the research obtained from 42 companies during 2011-2015 which has been listed on Indonesian share market and which also distributes dividends every year. Furthermore, the data analyzed using multiple regressions for panel data. The finding of the data analysis showed that the price for Indonesian companies’ share was considered to be cheap and even the price is higher than the price offered, the investor still want to buy it. Simultaneously the share price is insignificant affect to the frequency of share trading transactions of the company. Partially MBV, PER, MVA, EVA is significant to the stock trading frequency and it also significant to the volume of share trading. Therefore, it could be concluded that investors will assess the company fundamentally in making investment decisions.